2020
DOI: 10.3390/app10061913
|View full text |Cite
|
Sign up to set email alerts
|

BIM-LEAN as a Methodology to Save Execution Costs in Building Construction—An Experience under the Spanish Framework

Abstract: Current market conditions characterized by technological changes, increasing regulatory requirements and low funding make current construction management models obsolete. This tendency affects not only the private housing market but also public administration projects, which have large time and budget deviations across the board. As a result, new approaches are needed to improve the efficiency of the construction process, removing extra costs and delivering projects on time. The most representative trends in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 36 publications
0
15
0
2
Order By: Relevance
“…Some articles studied the interaction between lean construction and BIM and implied that a synergy exists between them [61]. Using Structural Building Information Modeling (S-BIM), a flexible environment is provided for collaboration and data exchange with the related fields to Set-based Design (SBD) implementation.…”
Section: Theme I: Lean and Bim Interactionmentioning
confidence: 99%
“…Some articles studied the interaction between lean construction and BIM and implied that a synergy exists between them [61]. Using Structural Building Information Modeling (S-BIM), a flexible environment is provided for collaboration and data exchange with the related fields to Set-based Design (SBD) implementation.…”
Section: Theme I: Lean and Bim Interactionmentioning
confidence: 99%
“…The interview results showed that the AEC industry has limited knowledge about the implementation of VE and BDA. Andújar-Montoya et al [92] stated that there are limited case studies that show the benefits of the implementation of these concepts together in projects. Likewise, the results indicated that the consideration of LM together with BIM is still in its infancy.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, national regulations could include specific construction details on how these problematic points could be more effectively addressed. This aspect would enable collaboration to minimise future construction costs and improve maintenance during the use phase-a matter, indeed, that is being given significant attention by a number of publications [42][43][44].…”
Section: Several Considerationsmentioning
confidence: 99%